Counterfeiting of medicine is no more incurable now - Hasan Abidi, Sayed Aliul (Indian Journal of Pharmacy Practice)
Counterfeit drugs are a menacing and deadly problem worldwide contributing to morbidity, mortality, toxicity, and drug resistance among the individuals. The proliferation of fake drugs is astounding, with over 100 countries reporting incidents of fake drugs according to a 2008 report from the Pharmaceutical Security Institute. The incidents of drug counterfeiting show no evidence of declining: some industry people suggest that the number of counterfeit medicines in market has increased to as much as 25% each year over the past several years.